Penggunaan Metode Guide Note Taking Berbantu Media Video dalam Pembelajaran Muatan Bahasa Indonesia di Sekolah Dasar pada Masa Pandemi Covid-19 - Cerianing Putri Pratiwi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This research aims to know the video-assisted note-taking guide method to improve the listening skills of elementary school 1st graders during the covid-19 pandemic. This study is a class action study. Teachers and elementary school 1st graders were the data sources for the study. The data collection techniques used are observations, interviews, and tests. The research procedures in each cycle are (1) action planning, (2) implementation of actions, (3) observations, (4) reflections. To analyze data using qualitative descriptive techniques and comparative descriptive. Based on the research that has been carried out, the research results can be known; namely, the improvement of listening skills of elementary school 1st-grade students after implementing the guide note-taking method assisted video. It is known that before being given the action, there are still many students who completed by 20%. After being given the action in cycle 1, students' grades increased by 75%. In this second cycle, all students have received complete grades.